Temporal modulation of host aerobic glycolysis determines the outcome of Mycobacterium marinum infection. Issue 96 (January 2020) - Kan, Yuanqing; Meng, Lu; Xie, Lingling; Liu, Lixia; Dong, Wenyue; Feng, Jintao; Yan, Yuchen; Zhao, Chao; Peng, Gang; Wang, Decheng; Lu, Mingfang; Yang, Chen; et al.
Abstract: Macrophages are the first-line host defense that the invading Mycobacterium tuberculosis (Mtb) encounters. It has been recently reported that host aerobic glycolysis was elevated post the infection by a couple of virulent mycobacterial species. However, whether this metabolic transition is required for host defense against intracellular pathogens and the underlying mechanisms remain to be further investigated. A pathogenic mycobacterial species, M. marinum, is genetically close to Mtb and was utilized in this study. Through analyzing cellular carbon metabolism of RAW 264.7 (a murine macrophage-like cell line) post M. marinum infection, a strong elevation of glycolysis was observed. Next, three glycolysis inhibitors were examined for their ability to inhibit mycobacterial proliferation inside RAW264.7 macrophages. Among them, a glucose analog, 2-deoxyglucose (2-DG) displayed a protective role against mycobacterial infection. Treatment with 2-DG at concentrations of 0.5 or 1 mM significantly induced autophagy and decreased the phagocytosis of M. marinum by macrophages. Moreover, 2-DG pre-treatment exerted a significantly protective effect on zebrafish larvae by limiting the proliferation of M. marinum, and such effect was correlated to tumor necrosis factor alpha (TNF-α) as the 2-DG pre-treatment increased the expression of TNF-α in both mouse peritoneal macrophages and zebrafish. On the contrary, the 2-DG treatment post infection did not restrain proliferation of M. marinum in WT zebrafish, and even accelerated bacterial replication in TNF-α −/− zebrafish. Together, modulation of glycolysis prior to infection boosts host immunity against M. marinum infection, indicating a potential intervention strategy to control mycobacterial infection. Highlights: Macrophages displayed an elevated glycolysis post M. marinum infection. 2-DG reduced phagocytosis and M. marinum burden inside macrophages. 2-DG pretreatment led to autophagy or apoptosis of RAW cells. 2-DG pre-treatment inhibited the proliferation of M. marinum in WT zebrafish. 2-DG accelerated M. marinum proliferation in zebrafish missing TNF-α.